Dampak Pandemi Covid-19 Terhadap Keberlangsungan Jaminan Kesehatan Nasional Bagi Pekerja Badan Usaha Swasta - Gusti Agung Sri Guntari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The Covid-19 pandemic has had a huge impact on the tourism sector. Private business entity workers are one of the segments in JKN participation affected by the Covid-19 pandemic.Research is a qualitative research that aims to explore information about the sustainability of the JKN program for private workers during the Covid-19 pandemic.Variables are explored regarding attitudes towards JKN contributions, attitudes towards health care facilities, attitudes towards BPJS Kesehatan and perceived of behavior control. Data collection was carried out by conducting indepth interviews with 2 people who were representatives of 2 private business entities appointed to manage JKN participation for workers.